Protocol for intervention study in reducing elevated blood pressure through intermittent fasting - Baharuddin, Dharina; Said, Mas Ayu; Abdul Majid, Hazreen (Journal of the Pakistan Medical Association, 2023)
Objective: To chart out a protocol for conducting an intervention-based study to compare the efficacy of intermittent fasting intervention and usual diet in reducing elevated blood pressure among working adults. Method: The quasi-experimental study with single-blinded parallel groups will comprise subjects from two civil departments. The intervention group will be required to conduct 2 days of fasting and 5 days of ad libitum diet in a week, while the control group will follow the usual healthy lifestyle. The largest sample size will be taken to achieve a power of 80% and an alpha value of 5%. Based on the 30% attrition rate, the total sample size needed in the study will be 140 participants, with 70 in each of the two arms. This study will use SPSS 24 for statistical analysis. Discussion: The study describes a unique protocol of intermittent fasting mimicking the Muslim Sunnah of fasting among people with elevated blood pressure. The findings will contribu to decrease blood pressure among those with elevated blood pressure. If proven to be effective, the intermittent fasting method would be useful for developing an effective programme to prevent elevated blood pressure among adults. The protocol will contribute to efforts to find whether or not intermittent fasting can improve elevated blood pressure as well as body weight, body mass index, waist circumference and nutrition status among adults. Clinical Trial Number: The study was registered with clinicaltrials.gov (NCT04953650). Key Words: Fasting, Blood pressure, Body mass index, Nutritional status, Indonesia.